2000
DOI: 10.1006/abbi.1999.1570
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Signal Transmission Involves Synergy between Discrete Structural Units of the Regulatory Subunit of Aspartate Transcarbamoylase

Abstract: Previous studies have shown that the S5′ β-strand (r93-r97) of the regulatory polypeptides of the aspartate transcarbamoylases (ATCases) from Serratia marcescens and Escherichia coli are responsible for their diverged allosteric regulatory patterns, including conversion of CTP from an inhibitor in E. coli to an activator in S. marcescens. Similarly, mutation of residues located in the interface between the allosteric and the zinc domains resulted in conversion of the ATP responses of the E. coli enzyme from ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…For both enzymes, substitution of some specific single amino acid residues can be sufficient to change the intensity of allosteric regulation. However, other authors found that these substitutions need not necessarily be positioned at a defined path for signal transduction but might cause global conformational changes due to changes in free energy (3,63).…”
Section: Atcasementioning
confidence: 99%
See 1 more Smart Citation
“…For both enzymes, substitution of some specific single amino acid residues can be sufficient to change the intensity of allosteric regulation. However, other authors found that these substitutions need not necessarily be positioned at a defined path for signal transduction but might cause global conformational changes due to changes in free energy (3,63).…”
Section: Atcasementioning
confidence: 99%
“…The nucleotides might change the stability of the interfaces as part of the primary effect, thereby influencing T-R transition on aspartate binding. On the basis of this, Liu et al proposed that changes in interfaces could influence allostery by altering the global energy of ATCase (63). ATP might induce a signal transduction chain via the R1-C1 interface, while CTP exerts its function via the R1-C4 interface (111).…”
Section: Models For the Allosteric Mechanismsmentioning
confidence: 99%